Validity and Reliability of the Child and Adolescent Version of the Iron Intake Scale (CIIS) as an Educational Tool - Satoko Okabe; Shinya Ito; Akemi Kameta; Aya Goto (SAGE Publishing, 2024)
Introduction/Objective: In Asia, 42% of young children suffer from iron deficiency anemia. Children have an increased requirement for iron intake because of growth and physical activity. Education plays an important role in anemia prevention and in ensuring children are aware of appropriate iron intake and the iron content of different foods. As a tool for this purpose, we adapted the adult version of the Revised Iron Intake Scale (RIIS) to create the Child and Adolescent Version of the Iron Intake Scale (CIIS), using illustrations to help children recognize the foods listed in the CIIS. We aimed to evaluate the validity and reliability of this new scale. Methods: We conducted a cross-sectional study using a self-administered questionnaire to examine the criterion-related validity of the CIIS. We used Spearman's rank correlation coefficient to compare iron intake estimated by the CIIS with that calculated by the Brief-type Diet History Questionnaire (BDHQ-15y), which assesses respondents' dietary habits over the past month and is standardized among Japanese children. The survey was repeated twice to examine reliability. Results: We found a moderate positive correlation for iron intake between the CIIS and BDHQ-15y, with a correlation coefficient of .52 (n = 258, P  < .001). Cronbach's alpha coefficient was .718. The CIIS reproducibility test yielded a correlation coefficient of .67. Conclusion: Our results indicated that the CIIS was valid, reliable, and reproducible. We therefore believe that the scale can be used to improve education about iron deficiency anemia and thereby reduce anemia rates among children and adolescents.